The Impact of Climate Change on the Food (In)security of the Siberian Indigenous Peoples in the Arctic: Environmental and Health Risks - Elena Bogdanova; Sergei Andronov; Andrei Soromotin; Gennady Detter; Oleg Sizov; Kamrul Hossain; Dele Raheem; Andrey Lobanov (Sustainability, 2021)
Climate change represents a global challenge that impacts the environment, traditional lifestyle and health of the Indigenous Peoples in the Arctic zone of Western Siberia and threatens their food security. Reindeer are an important food source for this population since reindeer herding products are used as traditional nutrition and effective preventive means and remedies for adapting to the cold and geomagnetic activity in the High North. Longer off-season periods, high summer and winter temperatures, melting ice, and forest and tundra fires have a significant impact on the trampling and degradation of reindeer pastures. These effects may lead to massive reindeer losses and changes in the traditional diet of the Indigenous Peoples in the Arctic, which result in increases in the prevalence of respiratory diseases, overweight and hypertension. This study applied a multidisciplinary approach based on ecological and medical research methods with the inclusion of socioeconomic analysis. The primary sources included data on the longitudinal dynamics of air temperature as a climate change indicator and reindeer livestock populations (1936–2018), consumption of reindeer products and physiological impacts on the Yamal Indigenous population collected during expeditions to the Arctic zone of Western Siberia in 2012–2018.